Gathering like terms together, this is equal to 5a + 3b + 7c.
It is the same as: 3b+4c which is an algebraic expression
(5a - 4b) + (2c - 3b - 6c) + a =5a - 4b + 2c - 3b - 6c + a =(5a + a) + (-4b - 3b) + (2c - 6c) =[ 6a - 7b - 4c ].
b + b + b + c + c + c + c = 3b + 4c
(5a)(2z) - (4a)(2c) + 15xz - 12xc group and factor each group = 2a(5z - 4c) + 3x(5z - 4c) factor again (5z - 4c)(2a + 3x)
2a + 2b = 26 2b + c = 22 ===> b = 11 - c/2 4c + 2b = 46 ===> b = 23 - 2c From the 2nd and 3rd equations: 11 - c/2 = 23 - 2c 22 - c = 46 - 4c 22 - 46 = -4c + c ===> -24 = -3c ===> c = 8 Substitute c=8 into the 3rd equation: b = 23 - 16 = 7 Substitute b=7 into the 1st equation: 2a + 14 = 26 2a = 12 ===> a = 6
2a + 4b + 8c = 2(a + 2b + 4c) You could also continue by factoring the inside of the parentheses a bit: 2a + 4b + 8c = 2(a + 2b + 4c) = 2(a + 2[b + 2c])
4c+1-5+2c = 6c-4.
4c+2 = 3c+9 4c-3c = 9-2 c = 7
It cannot be simplified any further so it is: 3a + 24b + 4c
This are the 6 different pencil cases: '''2B, HB, 4A, 4B, 2A, 4C.'''
17-3= 4c+3c c=2
48c + 408
An unbalanced reaction equation.
1st:-4c- 11- 4c=4c+12- 4c2nd:-8c- 11+ 11=21+ 113rd:-8c/-8+ 32/-8c=-4
Decorating Today, 1c,2a,3b,4c,5d,6a,7a,8c,9c,10d,11c,12c,13b,14a,15c,16c,17d,18b,19d,20b JUST TOOK THE TEST ALL ANSWER ARE RIGHT.GOOD LUCK ON THE OTHER.
4c-7 = 2c+11 4c-2c = 11+7 2c = 18 c = 9
Without further information, all we can do is simplify: 4c + 4d = 4(c + d)
5P + 111 + 136 + 20 = 4c + 4 5P + 267 = 4c + 4 -4 -4 5P + 263 = 4c You cannot cimplify it anymore, unless by 'c' you meant 'P'. 5P + 263 = 4P -5P -5P 263(-1) = -P(-1) -263 = P